PENGARUH MEDIA PEMBELAJARAN “REVIT” DAN MINAT TERHADAP HASIL BELAJAR SISWA PADA MATAPELAJARAN PRODUKTIF SMK JURUSAN TEKNIK KONSTRUKSI BATU BETON DI SMK 4 JAKARTA - Meliana, Dian; Iriani, Tuti; Rahmayanti, Henita (Jurnal Pendidikan Teknik dan Vokasional, 2020)
The purpose of this study is to study the effect of learning by using the media of “Revit” learning based on BIM (Building Information Modeling) on student learning outcomes as well as students’ learning interest in productive lessons especially on planning lessons for students of SMK Department of Construction of Batu Beton. The research used quantitative method. Selection of learning media “Revit” based on BIM (Building Information Modeling) to attract students’ interest in Department of Construction of Stone Construction of Concrete which initially used standart media that is excel for calculation of financing plan and simple building structure calculation. In this research, it is expected that students can more easily think in application in project which will be used as learning. Keywords: revit learning media, interest in learning, learning outcomes